Pelatihan Pembuatan Minuman Herbal Sari Buah Pandan Laut (Pandanus tectorius Park.) di Desa Hegarmanah, Kabupaten Lebak, Banten: indonesia - Wulandari, Asri; Setiani, Lusi Agus; Wardatun, Sri; Padhilah, Prasti Restu; Sunarya, M. Rustan; Malatabu, Shapira Mera (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Hegarmanah Village is one of the villages located in Lebak Regency, Banten with the area closest to the Warunghuni coast where sea pandan plants grow (Pandanus tectorius Park.). The sea pandan plant is a wild plant that grows a lot on the coast which is useful for withstanding the impact of the waves and has the effect of minimizing damage to the area behind the pandan vegetation. The community uses sea pandan fruit only for the leaves as raw material for making mats, but the fruit is often thrown away due to lack of knowledge. Sea pandan fruit contains secondary metabolite compounds that are beneficial for health. This community service activity (PKM) aims to increase the community's knowledge and skills in processing sea pandan fruit into herbal drinks to improve the community's health and economy. This PKM activity is carried out in the form of direct training with PKK women at Hegarmanah Village, housewife communities, Karang Taruna youth and village officials with the hope that the community can produce sea pandan juice herbal drinks sustainably and commercialize them as a typical Hegarmanah Village drink. Efforts to increase the selling value of abundant sea pandan fruit into various products with high competitiveness can be realized through continuous coaching and assistance by the community in collaboration with the team from the Pharmacy Study Program, Pakuan University.